2004
DOI: 10.1023/b:comh.0000026999.87728.2d
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Social Distance Toward People with Mental Illness

Abstract: Social distance is a multifaceted concept influenced by, e.g., socio-economic and cultural factors, but also by the respondent's general attitude toward (mental) health issues. These results suggest that more knowledge about mental illnesses, especially schizophrenia, may increase social distance. The findings presented here may help to focus anti-stigma campaigns not only on transmission of knowledge, but on integrating different approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
190
5
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(237 citation statements)
references
References 14 publications
33
190
5
9
Order By: Relevance
“…Evidence shows that attitudes held by health professionals are similar to the general public (Lauber et al, 2004) or more negative (Nordt et al, 2006). One study (sample size 4485) comparing health professionals and members of the public found stigmatising attitudes towards patients (Jorm et al, 1999), consistent with studies comparing health professional's attitudes towards physical illness and mental illness (Kakuma et al, 2011;Minas et al, 2011).…”
Section: Introductionmentioning
confidence: 70%
“…Evidence shows that attitudes held by health professionals are similar to the general public (Lauber et al, 2004) or more negative (Nordt et al, 2006). One study (sample size 4485) comparing health professionals and members of the public found stigmatising attitudes towards patients (Jorm et al, 1999), consistent with studies comparing health professional's attitudes towards physical illness and mental illness (Kakuma et al, 2011;Minas et al, 2011).…”
Section: Introductionmentioning
confidence: 70%
“…Society is more familiar with depression, and they tend to stigmatize schizophrenia more. [30][31][32] Beliefs and perceptions regarding MHS were operationalized based on the following subdomains: recovery (possibility of recovering from a mental illness and living a fulfilling life, 5 items); safety (posing a danger to others, 4 items); disclosure (willingness to disclose a personal mental illness, 3 items); separation (willingness to interact in social situations with a person living with mental illness, 10 items); and comfort (relating to or feeling comfortable with a person with mental illness, 5 items). Separation was measured using the 8-item Social Distance Scale (SDS), which is valid and reliable, in addition to two items derived from the literature.…”
Section: Methodsmentioning
confidence: 99%
“…A great deal of research has been conducted measuring social attitudes, especially in psychiatric epidemiology. These studies indicated the following three characteristics of social attitudes: (a) persons with schizophrenia are the most stigmatized and less expected to live and socialize in communities with others compared to those with other mental health problems (Durand-Zaleski, Scott, Rouillon, & Leboyer, 2012;Griffiths et al, 2006;Lauber, Nordt, Falcato, & Rössler, 2004); (b) the perceived dangerousness of persons with mental health problems is a primordial factor leading to negative social attitudes and stereotypes, particularly related to schizophrenia (Angermeyer, 2003;Durand-Zaleski et al, 2012); (c) social attitudes and the degree of tolerance toward people with schizophrenia orients the outcomes of their disorder (Warner, 1994). Additionally, people with schizophrenia feel that they experience prejudice related to their perceived dangerousness (González-Torres, Oraa, Arístegui, Fernández-Rivas, & Guimon, 2007).…”
Section: The Importance Of Social Acceptancementioning
confidence: 99%
“…The factors moderating and consequently reducing negative social attitudes are based on intimate experiences or interactions with persons who have schizophrenia or other chronic mental disorders (Desforges et al, 1991;Lauber et al, 2004;Yamaguchi et al, 2013;Yamaguchi, Mino, & Uddin, 2011). These interactions are referred to in the "contact hypothesis (Allport, 1979)."…”
Section: The Knowledge Hypothesismentioning
confidence: 99%
See 1 more Smart Citation